PENGEMBANGAN MEDIA PEMBELAJARAN BENTUK LAGU DENGAN MENGGUNAKAN MODEL PBL PADA MATERI KLASIFIKASI MAKHLUK HIDUP DI SMA NEGERI 1 MOTOLING - Meike Paat; Ferny Margo Tumbel; Yohanes Bery Mokalu (LPPM Politeknik Saint Paul Sorong, 2022)
This study aims to develop learning media in the form of songs using the Problem Based Learning/PBL model on the classification of living things at SMA Negeri 1 Motoling. The research method used is Research and Development (R&D) Borg and Gal. The results of the research are material expert validation (90%) and media expert validation (92%) as well as teacher responses (92%) and student responses classical (94%) showing that the learning media in the form of songs using the PBL model is very suitable to be used as a learning medium.